Dampak Lingkungan dan Keuntungan Finansial: Evaluasi Bio-Ekonomi dari Energi Terbarukan - Maryam; Syaifuddin Yana; Cut Hamdiah; Rahmi; Susanti; Samsul Ikhbar (Jurnal Serambi Engineering, 2024)
This article examines the environmental and financial impacts of renewable energy in a bio-economic framework. It examines how solar, wind and biomass energy can improve environmental sustainability and economic resilience. It uses a literature review, case studies of renewable energy deployment in different countries, and actual data on financial and environmental impacts. Investment in renewable energy technologies can save operating costs and provide long-term economic benefits. This article also discusses environmental benefits, including greenhouse gas reduction and air quality improvement. The gap analysis identified a lack of empirical data on the long-term impacts of renewable energy adoption on the bio-economy and a need for more research on the best strategies to promote it. This paper explains how renewable energy can boost the bio-economy and solve global economic and environmental problems. We hope that this paper will improve policy proposals and implementation tactics to optimise the bio-economic benefits of renewable energy.